EFEKTIVITAS EDUKASI DENGAN EMO-DEMO TERHADAP PENGENDALIAN KONSUMSI GARAM PADA IBU DI KELURAHAN ANDALAS - Eliya, Gina; Sidiq, Rapitos; Amos, John; Sumihardi, Sumihardi; Maria Silaban, Evi (Poltekkes Kemenkes Bengkulu, 2025)
Background: Hypertension at Andalas Public Health Center, Padang City, reached 33.63 percent in 2023. One controllable risk factor is excessive salt consumption. Housewives' knowledge plays an important role in this matter but remains limited due to the lack of promotional efforts. Purpose: This study aimed to determine the effectiveness of health education using the Emo-Demo method in controlling salt consumption among housewives in Andalas Subdistrict, East Padang District, Padang City. Methods: This research applied a mixed-method approach from January 28 to June 7, 2025. Qualitative data were collected through in-depth interviews with housewives, a nutrition program officer, a linguist, and a design expert. Qualitative sampling was conducted using non-probability sampling with a purposive sampling technique. The quantitative study used a quasi-experimental one-group pre-test and post-test design. Quantitative sampling was conducted using non-probability sampling with a total sampling technique. Data were collected from 70 housewives through a questionnaire and analyzed using univariate and bivariate methods with the Wilcoxon test. Results: The qualitative findings resulted in the development of a salt consumption Emo-Demo module adjusted to the needs of the target audience. Quantitative results showed an increase in the median knowledge score from 9.00 before the intervention to 14.00 after. The median attitude score increased from 44.00 to 49.00. Statistical tests showed significant differences in knowledge and attitude scores with a p-value less than 0.05. Conclusion: This study concludes that the Emo-Demo educational method is effective in enhancing housewives’ knowledge and attitudes toward controlling salt consumption.